2017
DOI: 10.21640/ns.v9i19.1019
|View full text |Cite
|
Sign up to set email alerts
|

Composición química y efecto antibacteriano in vitro de extractos de Larrea tridentata, Origanum vulgare, Artemisa ludoviciana y Ruta graveolens

Abstract: Composición química y efecto antibacteriano in vitro de extractos de larrea tridentata, origanum vulgare, artemisa ludoviciana y ruta graveolens Chemical composition and antibacterian effect in vitro of extracts of larrea tridentata, origanum vulgare, artemisa ludoviciana and ruta graveolens MétodoLos extractos se obtuvieron por destilación simple empleando alcohol etílico como solvente, la composición química se evaluó mediante cromatografía de gases. La actividad antimicrobiana de cada uno de los extractos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…As can be seen, several studies evaluated the antibacterial activity of L. tridentata; in some of them, the secondary metabolites associated with its antibacterial activity are reported. The chemical composition of L. tridentata indicates the presence of terpenes, saponins, tannins, quercetin, kaempferol, ellagic acid, gallic acid, methyl gallate, resorcinol, cinnamic acid, catechins, and lignans [19,42,45,61,[68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen, several studies evaluated the antibacterial activity of L. tridentata; in some of them, the secondary metabolites associated with its antibacterial activity are reported. The chemical composition of L. tridentata indicates the presence of terpenes, saponins, tannins, quercetin, kaempferol, ellagic acid, gallic acid, methyl gallate, resorcinol, cinnamic acid, catechins, and lignans [19,42,45,61,[68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…plant in ethanolic extract (70%). Other studies determined the content of quercetin, kaempferol, and Nordihydroguaiaretic acid (NDGA) in methanolic extracts and ethyl acetate fractions, determining concentrations of 8.67, 21.52, and 35.72, and 8.45, 11.89 and 16.51 mg of plant material, respectively [42,45,61,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their chemical composition, several studies have indicated that Ruta graveolens (rue) has potent antimicrobial activity. Besides, topical pharmaceutical fungicides were prepared from rue extracts [31,32,33,34,35,36,37,38,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment C3 (920 ppm) displayed the lowest fungal invasion, for B. cinerea was observed 15.5 % ± 3.31 and for F. oxysoprum 21.9 % ± 9.99, comparing with control without and with coating. Other authors [29] evaluated the efficacy of L. tridentata extracts against gram negative bacteria with promising results against Staphylococcus aureus. The present study demonstrated that it is possible prevent microorganism infection (B. cinerea and F. oxysoprum) in avocado by using bioactive coating.…”
Section: Resultsmentioning
confidence: 99%